The Development of Agritourism Village Area (case study at Kemuning Lor Village Arjasa Subdistrict Jember Regency) - Dewi Kurniawati; Rizal Perlambang CNAWP; Oktanita Jaya A.; M. Rizal Umami (International Journal of Science, Technology & Management, 2021)
One of the famous tourist attractions in Jember and became the icon of the agritourism village since 2009 in Jember Regency is Kemuning Lor Village, Arjasa subdistrict, Jember regency. This case makes the background of the research entitled the development of Agrowisata Village in Kemuning Lor Village, Arjasa District, Jember Regency. The objectives of this research are: 1) to know the economic empowerment of the community in the village of agritourism; 2) to identify the impact of tourism village development on community income; 3) to identify regional cooperation in the management of agritourism areas; and 4) to analyze the appropriate policy to the development of agritourism areas. This research uses descriptive research type. Research results are (1) the empowerment that already exists in the village of agritourism for example economic learning through the formation of skill groups with training models, economic learning through the formation of art groups, empowerment models through agent of change ,; (2) The impact of tourism village development on community income does not affect the income of the community. The increase of community income that occurred at the time of the study was due to the outside income of the farm, not the existence of an agritourism village. (3) Local government cooperation in managing the agritourism area included aspects: 1) Human Resource; 2) capital; 3) production; 4) distribution; 5) marketing; 6) competitiveness; and (7) Analysis of development policy of agritourism village in Kemuning Lor in, Arjasa sub-district, Jember regency as follows: tourism development policies especially agritourism villages already exist but have not run optimally in accordance with the vision and mission of the Tourism Office.